Cargo unloading problem: a quantitative modelling for arriving at optimum strategy. (20th January 2011) - Roy, Dilip; Bandyopadhayay, Asit
This paper presents a modelling approach for arriving at an optimum strategy for bulk cargo unloading in a port. This an important task faced by each and every port on each and every day. At present, no objective procedure is available in the literature. We have made an attempt to formulate the unloading problem in terms of five alternative strategies and derive expressions for their respective costs, so that optimal unloading strategy can be identified and adopted. This involves handling of the situations in the stochastic domain. A case study has been added on Kolkata port for demonstration purpose.